Analysis of oil palm clones, their suspension calli and regenerants via flow cytometry (FCM) and rDNA- fluorescence in situ hybridiSsation (rDNA-FISH) - Midin, Mohd Razik; Rosli, Samsul Kamal; Hashim, Ahmad Tarmizi; Nulit, Rosimah; Madon, Maria (Malaysian Palm Oil Board, 2013)
Clonal propagation of palms with good traits is desirable for the oil palm industry. In this study, flow cytometry (FCM) and 18S-25S ribosomal DNA-fluorescence in situ hybridisation (rDNA-FISH) were utilised to analyse genetic variation in adult clonal palms, their respective suspension cultures and regenerant plantlets. The genome sizes estimated by FCM for the four adult clonal palms (using leaf samples from Frond-1) varied from 2C=2.59±0.19 pg to 2.91±0.14 pg and for their respective regenerants, the genome size varied from 2C=2.14±0.21 pg to 3.05±0.11 pg. The genome size of oil palm suspension cultures could not be analysed by FCM due to the low nuclei population, which was less than 1000. The rDNA-FISH analysis showed two hybridisation signals on interphase nuclei of suspension culture calli and regenerant plantlets, hence indicating the diploid ploidy level. Adult clonal palms with their suspension culture calli and regenerants therefore showed a similar ploidy level. However, the measurement of genome size was found to vary between the adult clonal palms and their regenerants.